Natural Treatment of Stormwater Runoff - Armentrout, Taz; Barbeau, Nicholas; Kincaid, Jordan; Phillips, Nathan; Pittore, Ephraim; Hunsucker III, James F.; Smith, James E. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
In the Northeastern region of the United States, there is a growing problem in the collection andtreatment of stormwater runoff. In recent years the region has experienced record amounts ofrainfall with the projections pointing to this trend continuing. The Sanitation Department in mostof these areas is responsible for the collection of this stormwater, meaning that the runoff iscombined with, and treated as wastewater. Most of the current water treatment systems cannothandle these increased demands during large storms and as result hundreds of thousands ofgallons of waste are dumped into the surrounding rivers and streams during and shortly afterthese large storms.The US Environmental Protection Agency (EPA) is levying fines and promulgating additionalregulations for these violations, so a long term solution is necessary. The proposed method ofaddressing these needs involves mimicking the natural water cycle which would naturally allowthe water to be absorbed into the ground and then evaporated as opposed to flowing directly intothe sanitation system. This study looked at a local urbanized region, Pittsburgh Pennsylvania, asa case study considering the locale and its urbanization, the current infra-structure, and thecurrent and future requirements for storm water runoff mitigation.The study defined the problem, considered the current legal implications, and then looked at thetypes of technologies that could be implemented to address this problem. The technologyultimately recommended would be a roof spray technology that is capable of collecting theexcess stormwater runoff, storing it, and then spraying it onto a roof where it would beevaporated. This system would reduce the excess water runoff created during storms that thesanitation systems cannot adequately handle. The concept for this runoff solution is providedwith an analysis of the actual issues underlying these runoff problems.